2017
DOI: 10.1364/ol.42.003193
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic forward-viewing optical coherence tomography and angiography with MHz swept source

Abstract: Endoscopic optical coherence tomography (OCT) instruments are mostly side viewing and rely on at least one proximal scan, thus limiting accuracy of volumetric imaging and en face visualization. Previous forward-viewing OCT devices had limited axial scan speeds. We report a forward-viewing fiber scanning 3D-OCT probe with 900 µm field of view and 5 µm transverse resolution, imaging at 1 MHz axial scan rate in the human gastrointestinal tract. The probe is 3.3 mm diameter and 20 mm rigid length, thus enabling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…For example, OCT showed normal submucosa underneath a rectal polyp near the dentate line and altered its management from a full thickness resection to a less invasive endoscopic mucosal resection (EMR) [76]. High-resolution en face colon images from OCT are analogous to the traditional magnified endoscopic view, but do not require contrast agents; they also yield clinically powerful multi-depth visibility [77]. Thus, OCT has the potential to improve polyp detection and management.…”
Section: Colonmentioning
confidence: 99%
“…For example, OCT showed normal submucosa underneath a rectal polyp near the dentate line and altered its management from a full thickness resection to a less invasive endoscopic mucosal resection (EMR) [76]. High-resolution en face colon images from OCT are analogous to the traditional magnified endoscopic view, but do not require contrast agents; they also yield clinically powerful multi-depth visibility [77]. Thus, OCT has the potential to improve polyp detection and management.…”
Section: Colonmentioning
confidence: 99%
“…The volumetric OCT imaging in the colon also allows visualization of en face features for better differentiation of the diseases. 87 Recently, Liang et al 88 developed a forward-viewing OCT probe using a piezoelectric actuator and demonstrated high-resolution en face colon images that are analogous to magnified endoscopic view without requiring contrast agent and providing multidepth visualization. Figure 7 shows in vivo volumetric images from a hyperplastic polyp at an imaging speed of 2 volumes per second, which is an encouraging example of in vivo polyp assessment using OCT.…”
Section: Inflammatory Bowel Disease and Polyps Screening Investigatiomentioning
confidence: 99%
“…However, this probe has a relatively small field of view (FOV) of 800 μm . First endoscopic OCTA images were also recently demonstrated using a larger probe over a FOV of only 450 μm . No 3D images have been demonstrated and the technique was not sensitive enough to detect small vessels due to a strong noise background present in the images .…”
Section: Introductionmentioning
confidence: 99%